1996
DOI: 10.1039/cc9960001279
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of trivalent stannyl cations in solution

Abstract: It is shown by NMR spectroscopy that no free trigonal stannyl cations in solution have been observed to date as also expected from theoretical ab initio IGLO calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 11 publications
4
22
0
Order By: Relevance
“…[66] www.eurjic.orgnBu 3 SnOTf (4) and 6 with H 2 : No reaction was apparent by 119 Sn NMR spectroscopy at ambient temperature after 2 h or at 50°C after a further 18 h. Only unreacted 4 was observed in solution ( 119 Sn NMR: δ = 151 ppm). [70] B(C 6 F 5 ) 3 (1) and 5 with H 2 : No reaction was apparent by 11 B NMR spectroscopy at ambient temperature after 2 h with only 1 ( 11 B NMR: δ = 58.6 ppm) being observed in solution. [61] The mixture was then heated to 50°C for a further 18 h, after which analysis by 11 B NMR spectroscopy exhibited two signals: a minor peak corresponding to an unknown product (δ = 3.5 ppm) and a major peak arising from [HB(C 6 F 5 ) 3 ]…”
Section: And 26-di-tert-butylpyridine (5) With Hmentioning
confidence: 95%
See 1 more Smart Citation
“…[66] www.eurjic.orgnBu 3 SnOTf (4) and 6 with H 2 : No reaction was apparent by 119 Sn NMR spectroscopy at ambient temperature after 2 h or at 50°C after a further 18 h. Only unreacted 4 was observed in solution ( 119 Sn NMR: δ = 151 ppm). [70] B(C 6 F 5 ) 3 (1) and 5 with H 2 : No reaction was apparent by 11 B NMR spectroscopy at ambient temperature after 2 h with only 1 ( 11 B NMR: δ = 58.6 ppm) being observed in solution. [61] The mixture was then heated to 50°C for a further 18 h, after which analysis by 11 B NMR spectroscopy exhibited two signals: a minor peak corresponding to an unknown product (δ = 3.5 ppm) and a major peak arising from [HB(C 6 F 5 ) 3 ]…”
Section: And 26-di-tert-butylpyridine (5) With Hmentioning
confidence: 95%
“…Removal of all volatiles from the filtrate afforded a colourless oil, which was also analysed by multinuclear NMR spectroscopy. The absence of resonances at δ = -40.0, 1.7 and 172 ppm in the 11 B, 31 P and 119 Sn NMR spectra, respectively, indicated complete consumption of both 4 [70] and 23. [71] However, there were no signals in the former two spectra that could be assigned to any of the expected dehydrogenation products, [36] Further evidence for the occurrence of a reaction other than dehydrogenation was apparent from the observation of phosphorus-tin coupling (J P-Sn = 196 Hz) in both the 31 P and 119 Sn NMR spectra.…”
mentioning
confidence: 95%
“…29,61 Kira et al also prepared the n-Bu 3 Sn + derivative as its TFPB − salt, using the traditional hydride transfer method (Section 1.2.2, Scheme 1.2, C) and reported the low-field resonance of the cationic Sn atom to be 356 ppm. 7 This conclusion was, however, later questioned by Edlund et al, 41 who pointed out that the values of 360 60 and 356 7 ppm assigned to the cationic Sn atom are better attributed to the covalently bound arene complexes, quite similar to the case discussed above of the silylium ions vs Wheland σ -complexes problem. On the basis of an empirical correlation between the 29 Si and 119 Sn NMR chemical shifts, the resonance of the truly free trigonal-planar Me 3 Sn + cation was expected to be observed at a much lower field of 1500-2000 ppm, a conclusion that also gained support from theoretical calculations.…”
Section: Scheme 110mentioning
confidence: 96%
“…They concluded that the naked cations do not exist in solution and what were previously observed were, in fact, donor-acceptor complexes with solvent molecules. 8 In 1996, Arshadi et al 1 employed "'Sn/^Si NMR shift correlations to argue also that no naked triorganostannyl cations had been observed in solution to date.…”
Section: Introduction Triorpanostannyl Cationsmentioning
confidence: 98%